2021
DOI: 10.1007/s40520-021-01969-x
|View full text |Cite
|
Sign up to set email alerts
|

Surgical aortic valve replacement in elderly patients: effects on physical performance, cognitive function and health-related quality of life

Abstract: Background Surgical aortic valve replacement (SAVR) is still the gold standard for treating aortic valve stenosis (AVS). Its effectiveness has been extensively examined in terms of perioperative mortality, but its impact on overall health has received much less attention. Aims To assess the physical performance, cognitive status, and health-related quality of life of elderly patients undergoing SAVR, in the short, medium and long term. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 35 publications
0
2
1
Order By: Relevance
“…Limited data exist for cognitive function changes occurring after SAVR. De Rui et al (7) showed a significant worsening of the patients' condition in the MoCA test performed 1 year after SAVR; however, this finding is not confirmed in our series. Basically, our data support the concept that the removal of aortic valve obstruction is beneficial in neurocognitive terms, regardless of the procedure.…”
Section: Discussioncontrasting
confidence: 97%
See 1 more Smart Citation
“…Limited data exist for cognitive function changes occurring after SAVR. De Rui et al (7) showed a significant worsening of the patients' condition in the MoCA test performed 1 year after SAVR; however, this finding is not confirmed in our series. Basically, our data support the concept that the removal of aortic valve obstruction is beneficial in neurocognitive terms, regardless of the procedure.…”
Section: Discussioncontrasting
confidence: 97%
“…One certain factor is that elderly (>70 years) patients referred to AS procedures have a pre-procedural impairment of neurocognitive function. When tested with a Montreal Cognitive Assessment (MoCA), 70% of the patients have a MoCA score <26, which is considered the cutoff value for normal cognitive function (7). This pattern finds different causative factors such as comorbidities, previous neurological events, dementia, and other neurological diseases; however, inadequate cerebral blood flow may be a contributor, especially in elderly subjects (8).…”
Section: Introductionmentioning
confidence: 99%
“…Over time, with the improvement of the surgical procedure, the risks for such procedure have decreased and survival and quality of life of patients have accordingly improved. [ 6 ] Various techniques employed to replace aortic valve include the use of bioprosthetic valve sourced from using animal valve or pericardium, the use of mechanical valve made by tolerable synthetic materials for the body such as metal and carbon, pulmonary autograft (removing the aortic valve and replacing with patient's own pulmonary valve) and prosthetic valve replacement by TAVR. [ 7 8 ]…”
Section: Introductionmentioning
confidence: 99%